Expenditure Patterns and Women’s Status in Households in Bengkulu Province - Tyaningsih, Elis; Sukiyono, Ketut; Windirah, Nola (AGRITROPICA : Journal of Agricultural Sciences, 2024)
This study aims to 1) analyze the pattern of household food and non-food expenditure in Bengkulu Province; 2) analyze the factors that influence household expenditure patterns in Bengkulu Province; 3) Analyze the status of women in households in Bengkulu Province. This research was conducted in Bengkulu Province. This study uses secondary data from the SUSENAS (National Socioeconomic Survey). The analysis model used in this study is OLS multiple linear regression using the Shazam application. The results of the study show 1) that the most significant expenditure is on food expenditure, namely 52%, while non-food expenditure is 48%; 2) the educational status of women has a higher percentage of 40%, equal to 34% and lower than men by 26%. Meanwhile, the employment status of women has a higher percentage of 46%, equal to 41% and lower than men by 13%; 3) the factors that influence the pattern of household food expenditure are the purchase price of fish, the purchase price of cigarettes and the number of family members. The factors that influence the pattern of non-food expenditure are the purchase price of fish, the purchase price of eggs, the purchase price of cigarettes, women's employment status, women's education status, number of family members, total asset ownership, and home ownership status.